Microbial Transformation of Chlordecone and Two Transformation Products Formed During in situ Chemical Reduction - Hellal, Jennifer; Saaidi, Pierre-Loïc; Bristeau, Sébastien; Crampon, Marc; Muselet, Delphine; Della-Negra, Oriane; Mauffret, Aourell; Mouvet, Christophe; Joulian, Catherine (Frontiers in Microbiology, 2021)
Chlordecone (CLD) is a very persistent synthetic organochlorine pesticide found in the French West Indies. Recently published work has demonstrated the potential of zero-valent iron to dechlorinate CLD by in situ chemical reduction (ISCR) in soils under water-saturated conditions, forming mono- to penta-dechlorinated CLD transformation products. These transformation products are more mobile than CLD and less toxic; however, nothing is known about their further degradation, although increasing evidence of CLD biodegradation by bacteria is being found. The present study began with the enrichment from wastewater sludge of a CLD-transforming community which was then inoculated into fresh media in the presence of either CLD or two of the main ISCR transformation products, 10-monohydroCLD (-1Cl-CLD) and tri-hydroCLD (-3Cl-CLD). Carried out in triplicate batches and incubated at 38°C under anoxic conditions and in the dark, the cultures were sampled regularly during 3 months and analyzed for CLD, -1Cl-CLD, -3Cl-CLD, and possible transformation products by gas chromatography coupled to mass spectrometry. All batches showed a decrease in the amended substrates (CLD or hydroCLD). CLD degradation occurred with concomitant formation of a nine-carbon compound (pentachloroindene) and two sulfur-containing transformation products (chlordecthiol, CLD-SH; methyl chlordecsulfide, CLD-SCH3), demonstrating competing transformation pathways. In contrast, -1Cl-CLD and -3Cl-CLD only underwent a sequential reductive sulfidation/S-methylation process resulting in -1Cl-CLD-SH and -1Cl-CLD-SCH3 on the one hand, and -3Cl-CLD-SH, -3Cl-CLD-SCH3 on the other hand. Some sulfur-containing transformation products have been reported previously with single bacterial strains, but never in the presence of a complex microbial community. At the end of the experiment, bacterial and archaeal populations were investigated by 16S rRNA gene amplicon sequencing. The observed diversity was mostly similar in the CLD and -1Cl-CLD conditions to the inoculum with a dominant archaea genus, Methanobacterium, and four OTU affiliated to bacteria, identified at the family (Spirochaetaceae) or genus level (Desulfovibrio, Aminobacterium, and Soehngenia). On the other hand, in the -3Cl-CLD condition, although the same OTU were found, Clostridium sensu stricto 7, Candidatus Cloacimonas, and Proteiniphilum were also present at > 2% sequences. Presence of methanogens and sulfate-reducing bacteria could contribute to sulfidation and S-methylation biotransformations. Overall, these results contribute to increasing our knowledge on the biodegradability of CLD and its transformation products, helping to progress toward effective remediation solutions.